Phenomenological Study of ESL Students’ Lived Experiences with AI-Powered Language Learning Tools - Jamaine Cristobal; Bryan Credo; Juquir Esguerra; Russel Mhilo Mabagos; Cielo Mae Mamaril; Pia Bianca Ordoña; Jennelyn Lacar Raymundo (PT. Global Research Collaboration, 2025)
This qualitative phenomenological study explored the lived experiences of ESL students at the College of Education, Isabela State University-Echague Campus, in using AI-powered language learning tools such as Grammarly, Gemini Bard, ChatGPT, QuillBot, and Bing AI. It responds to the growing need to understand how these emerging tools are transforming language learning. This study was anchored in Lev Vygotsky’s social constructivist framework, focusing not just on tool effectiveness, but on how learners perceive, interact with, and are challenged by these tools in the context of language learning. There were 25 respondents selected among the first to fourth year Bachelor of Secondary Education English students, specifically those with experience using AI-powered language learning tools. The Interpretative Phenomenological Analysis (IPA) was used to analyze the data. Findings revealed that AI tools enhanced students’ grammar, vocabulary, reading comprehension, and writing skills through personalized feedback and support. However, it also revealed significant issues such as over-reliance, data privacy concerns, and issues with output accuracy and bias. Therefore, the study highlights the importance of a student-focused capacity development program that equips ESL learners with digital literacy, critical thinking, and responsible AI use skills to maximize the benefits and minimize the drawbacks of AI-powered tools in language learning.